Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Kinerja Keuangan - Faisal, Muhammad Asrullah; Nur, Andi Nirwana; Hamzah , Firda Faradyba (Center of Economic Students Journal, 2023)
This study aims to analyze the effect of profitability, liquidity, and leverage on the financial performance of PT Kimia Farma Tbk for the 2019–2023 period. The research is motivated by the significant decline in financial performance during 2022–2023, marked by substantial losses and fraud cases that affected public trust. The independent variables are profitability measured by Return on Assets (ROA), liquidity measured by Current Ratio (CR), and leverage measured by Debt to Asset Ratio (DAR). The dependent variable, financial performance, is measured using Earnings Per Share (EPS). This research applies a descriptive quantitative method using secondary data from annual financial statements obtained from the Indonesia Stock Exchange. Data analysis was conducted using multiple linear regression and partial tests to examine the effect of each variable individually. The results indicate that ROA has a significant positive effect on EPS, whereas CR and DAR have no significant effect on EPS. These findings suggest that the company’s ability to generate profit from its assets is the main driver of financial performance improvement, while liquidity levels and debt-based funding structures have not shown a substantial impact. The results are expected to provide valuable insights for management, investors, and stakeholders in making strategic decisions to enhance the company’s financial performance.